Impact of social networks on the purchase decision of women in the cosmetics sector - Flores Barahona, Milagros; García Salcedo, Anaclaudia Antonella; Lazaro Acero, Heli Modesto; Suxe-Ramírez, María Alicia (LACCEI, 2025)
This study addresses the issue of how social media has changed the traditional dynamics of selling cosmetic products. The objective was to determine the relationship between the use of social media and the purchasing decision of young women in Nuevo Chimbote during 2024. With a quantitative approach and a descriptive-correlational design, a sample of 80 women between 20 and 29 years old was used. The data was also collected through a questionnaire in Google Forms and processed with SPSS. The results showed a moderate positive rating (r = 0.435) between social media and purchasing decision, with significance of α = 0.001, suggesting that interaction on platforms such as Facebook and Instagram is positively related to the purchasing behavior of this population group.